The aspect of the corrosion pitting with fretting fatigue on aluminum alloy: An aerospace structural failure or a nuclear safety phenomenon - Quazi Md Zobaer Shah; Mohammad Asaduzzaman Chowdhury; Md Arefin Kowser (Results in Engineering, 2022)
Since wear and other surface decaying processes like corrosion pitting can risk the lifespan of valuable properties as well as infrastructures, surface modification and other fatigue reducing attempts are being adopted for Aluminum alloys in various sophisticated applications like aerospace or nuclear components. In this research work, fretting fatigue and artificial pitting effect on heat treated Al–Mg–Si alloy (Al 6061-T6) has been studied. Experimental observations have been authenticated by developing a FEM model using simulation software ANSYS 14.5. Fretting causes a noticeable reduction in fatigue life at high cycle fatigue tests. However, it is difficult to differentiate between fretting and normal fatigue curve line at low cycle fatigue. Fracture surface schematic shows how fretting affects crack initiation to final rupture. Interestingly, it has been found that pitting reduces the lifetime of Aluminum abruptly than normal and even fretting fatigue. This study suggests more concentration on pitting by corrosion or others as well as geometry irregularities than fretting aspect comparatively.